1990
DOI: 10.1093/mutage/5.5.491
|View full text |Cite
|
Sign up to set email alerts
|

DNA synthesis in radiation-induced micronuclei studied by bromodeoxyuridine (BrdUrd) labelling and anti-BrdUrd antibodies

Abstract: DNA synthesis in radiation-induced micronuclei of Chinese hamster cells was studied as a function of time after irradiation using pulse labelling of cells with bromodeoxyuridine (BrdUrd) and an immunofluorescence technique with anti-BrdUrd antibodies. It was shown with this technique that DNA synthesis in micronuclei corresponds with DNA synthesis in nuclei during S phase in approximately 98% of the micronuclei. The presence of radiation-induced micronuclei that are too large to be produced by acentric fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Therefore, micronuclei may be formed from chromosomal material fragmented during mitosis and not incorporated in daughter nuclei at completion of telophase. Micronuclei are then coated with a nucleus envelope, and their DNA is often transcriptionally active and undergoes replication (Nusse, 1981;Kramer et al, 1990). The frequency of the presence of micronuclei serves as a measure of in vitro or in vivo exposure to mutagens and carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, micronuclei may be formed from chromosomal material fragmented during mitosis and not incorporated in daughter nuclei at completion of telophase. Micronuclei are then coated with a nucleus envelope, and their DNA is often transcriptionally active and undergoes replication (Nusse, 1981;Kramer et al, 1990). The frequency of the presence of micronuclei serves as a measure of in vitro or in vivo exposure to mutagens and carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that fragments or breaks whose termini were not repaired might be subject to nuclease degradation resulting in gene loss. In the case of persistent fragments it has been shown that those incorporated into micronuclei often retain the capacity to synthesise DNA (Pincu et al 1985, Kramer et al 1990). However, in an unirradiated Burkitt's lymphoma line, Kato and Sandberg (1968) observed spontaneously-occurring micronuclei that were unable to synthesize RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, micronuclei formation has paved a pathway for stabilization of genetic structure. It has been reported that micronuclei are able to synthesize DNA (Kramer et al 1990) and there is ultra-structural similarity between micronuclei and cell nuclei (Schiffmann and De Boni 1991).…”
Section: Discussionmentioning
confidence: 99%